Implementation of a Modern Simping Press Machine to Enhance Product Value in the Kelompok Wanita Tani Bunga Tanjung, Tanjungsari Village, Purwakarta Regency - Zakaria, Diky; Subekti, Sri; Fauziah, Dini; Arifin, Riyadhil Haqqy; Nugraha, Rifki Destrizal; Herlina, Nina; Jamilah, Dewi Siti; Asradinto, Faris Fathan (Institut Teknologi Nasional, Bandung, 2025)
This community service initiative was designed to enhance the production efficiency and marketing capacity of simping products developed by the Women Farmers Group (Kelompok Wanita Tani, KWT) Bunga Tanjung in Tanjungsari Village, Purwakarta. The program employed a participatory action research approach. The main intervention involved the introduction of a modern simping press machine featuring an ergonomic design and a dual-heating system, which allows for faster, more efficient production with consistent baking quality. Additionally, the team developed a comprehensive handbook that includes operational guidelines for the machine, formulations for new flavor variants, and digital marketing strategies. The results demonstrated that the implementation of this technology significantly improved both the productivity and quality of simping while reducing the physical workload of the participating members. The strong enthusiasm and positive responses from KWT members indicate that this appropriate technology effectively addressed their needs. Overall, the program contributes to strengthening the village-based creative economy through local culinary innovation and advancing women’s empowerment within micro, small, and medium enterprises (MSMEs).